The Effect of Zirconia Material for Dental Implant To Osseointegrated Process - Maya Sari Dewi; Hendri Peornomo (SONDE (Sound of Dentistry), 2020)
Objective: Tooth lost is the one of mostly case in dentistry. Dental implant are the proper and fast procedure to rehabilitated full or partial edentulous ridge. Many research and clinical study said that the successful of dental implant application are depend on osseointegration which considered by anatomical of the bone structure with implant or mechanical feature of implant. Dissucion : The composition of material and topographic surface are the important thing in osseointegration process . For many patient, Titanium give a good results, but some of patient worried because it can make a grey line in sub gingival or across the ridge which have a thin bone and soft gingival structure, So with zirconia implant hopefully that grey line doesn’t appear. Both of titanium and zirconia are very strong, Titanium have a high flexibility and fracture resistence but, zirconia have a low elasticity, which can cause a micro fracture. Conclusion : Zirconia implant have a good esthetics and looked naturally.